Mechanical and Degradation Properties of Thermoplastic Starch Reinforced Nanocomposites. (27th January 2022) - Behera, Ajaya Kumar; Srivastava, Rohit; Das, Anath B.
Abstract: Fossil oil derived materials exhibit non‐degradable properties with a limited availability. To overcome these limitations, a biodegradable starch/poly(ε‐caprolactone) based Coloisite‐20A nanocomposites are developed in this research study. The overall performance of these newly developed nanocomposite materials is deeply investigated. First, the morphological analysis of the nanocomposites is examined using X‐ray diffraction, transmission electron microscopy, and atomic force microscopy. Thereafter, mechanical performance of the nanocomposites is analyzed through tensile and flexural tests. The water‐based contact angle and sorption testing are conducted to confirm the hydrophobic or hydrophilic nature of the nanocomposite. Finally, the degradation behavior of this nanocomposite is estimated by the soil‐burial tests followed by Fourier transform infrared analysis, field emission electron microscopy, and transmission electron microscopy. All the experiments are performed for the control and the test samples. The developed nanocomposites exhibit maximum tensile strength of 6.30 MPa with a water sorption of 6.08% for a 24 h of water immersion tests. On the other hand, the soil‐burial degradation reflects a maximum weight loss of 45.4% after 56 days of degradation period. Hence, moderately hydrophobic, low strength, biodegradable hybrid nanocomposites are developed to counter the use of non‐degradable plastic composites. Abstract : In this work, a moderately hydrophobic and biodegradable Cloisite 20A reinforced thermoplastic starch composite is developed and characterized. The tensile strength of the composite is 6.3 MPa and water absorption of the 3 wt% clay composite is found to be 6.08%. After 56 days, the composite lost 30.2% of its original weight.